Macrophage lipid efflux regulates the tumour microenvironment in early‐stage lung adenocarcinoma - Yujie Zheng; Yuan Wang; Yalin Wang; Yue Shi; Hui Kong; Shaohua Lu; Yong Zhang; Jie Hu; Jian Zhou; Xiangdong Wang; Meng Xiang; Qiong Liu; et al. (Clinical and Translational Discovery, 2026)
Background Metabolic rewiring influences macrophage functions in tumours. However, metabolic heterogeneity of macrophages in early‐stage lung adenocarcinoma (LUAD) has not been fully understood. Methods Based on single‐cell transcriptomic analysis on lung tissues from human subsolid pulmonary nodules and from Kras G12D and Kras G12D Tgfbr2 −/− mice, we unveiled alterations of macrophage states in LUAD. We applied cell migration and invasion assays to examine effects of ATP binding cassette subfamily A member 1 (ABCA1) in macrophages on tumour progression. In addition, using coculture system, we explored its role in macrophage polarisation. Results Major macrophage subsets underwent shifts during tumourigenesis, as alveolar macrophages reduced sharply and their interstitial counterparts increased. Of note, tumour‐associated macrophages (TAMs) are metabolically rewired, with a subset enhancing lipid efflux predominated in both human and murine tumour. It was characterised by high expression of the lipid transporter, ABCA1. Targeting ABCA1 by its inhibitor probucol suppressed TAM capacity to induce tumour cell migration and invasion. In addition, inhibiting ABCA1 was associated with dampened immunosuppression of TAMs by shifting them to a M1‐like phenotype. Conclusions We uncovered TAM heterogeneity in early‐stage LUAD and proposed ABCA1 as a potential target for metabolic rewiring, which manipulated macrophage polarisation states and its effects on tumour aggressiveness.